The neuropsychiatry of epilepsy - Trimble, Michael R.; Schmitz, Bettina, 1960- (Cambridge University Press, 2002)
Michael Trimble and Bettina Schmitz have assembled a multi-national team of experts to review and explore the interface between epilepsy and behaviour disorders. Coverage is broad-ranging and offers both a diagnostic and management perspective. This will be essential reading for all professionals engaged in the treatment of epileptic patients.